PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERORIENTASI MODEL PEMBELAJARAN DISCOVERY LEARNING (DL) UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR KREATIF SISWA PADA MATERI BIOTEKNOLOGI KELAS XII SMA - Setiadewi, Feli Setiadewi; Suryawati, Evi Suryawati; Mahadi, Imam Mahadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The aim of this research was to develop discovery learning-oriented student worksheets to improve students’ creative thinking skills in biotechnology topic on grade XII shs. The research held on December 2014 until March 2015. The research used Research and Development with ADDIE model as the method. Development was held in laboratory of Biology Education Riau University and limited trial was held in MAN 2 Model Pekanbaru.Validation sheet, respondent sheet and observation sheet of creative thinking skills were used as data collecting instruments. Validation sheet consist of 18 items and 4 aspects, there are didactic, construction, technique and creative thinking skills. The results of the validation of experts obtained the following data: didactic 3.43 (very valid), construction 3.62 (very valid), technique 3.75 (very valid) and creative thinking skills 3.69 (very valid). Discovery learning oriented worksheets that have been developed potentially to improve student’s creative thinking skills on biotechnology topic for grade XII shs. Worksheets need to be continued until implementation and evaluation steps to make sure the quality of worksheet product developed. Key words: biotechnology, discovery learning, student worksheet, creative thinking skill